Analysis of the Impact of Termination of Employment on Employee Finances - Harmen, Hilma; Syahreza, Dina Sarah; Hutagalung, Gracella Rosnah S; Sahfitri, Serly; Wulandari, Artika; Siregar, Ade Mima Zakia; Limbong, Novia Grace Cristin (LPPPIPublishing, 2024)
Companies can help their employees better manage their finances through employee benefits programs such as financial counseling and retirement planning assistance. These programs provide employees with the necessary knowledge and tools to make wise financial decisions, thereby improving their financial management capabilities and positively impacting their long-term financial well-being. A good and stable working relationship provides many financial benefits, such as income stability, additional benefits, and company support in professional development and financial management. This research uses a qualitative method with data collection based on a thorough literature search and literature sources. In addition, the psychological and emotional impact of layoffs also needs to be considered as it can threaten employees' quality of life and mental health. Therefore, it is important for companies and governments to provide support and assistance programs for employees affected by layoffs to help them recover and achieve financial stability and well-being in the future. Layoffs can have serious consequences including loss of income, cash flow disruption, debt, loss of social security and health insurance, and psychological distress. The negative impact of layoffs is not only limited to finances, but also includes stress, anxiety, depression and disruption of personal relationships. Therefore, it is important for companies and governments to work together to provide support and assistance programs to employees affected by layoffs.